Role Stress, Kompensasi Finansial, Motivasi Kerja dan Kepuasan Kerja - Riska Wulandari; Ida Bagus Teddy Prianthara (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe purpose of this study is to determine the effect of role stress, financial compensation and work motivation on job satisfaction. This research was conducted at Rural Bank in Denpasar. The population  in this research  is all employees  of BPR in Denpasar  City. The sampling technique used accidental sampling obtained on 80 samples used in this research. The results of this study indicate that there is a negative and significant influence between role stress on work  motivation.  The  existence  of  positive  and  significant  influence  between  financial compensation to motivation work is a negative and significant influence between role stress and  job  satisfaction.   The  existence  of  positive  and  significant  influence  of  financial compensation on job satisfaction. The existence of positive and significant influence between work motivation on job satisfaction. The value of direct influence is greater than the value of indirect influence this means that the motivation variable does not mediate the influence of role stress  on job satisfaction.  The value  of direct  influence  is greater  than  the value of indirect influence this means that the motivation variable does not mediate the influence of role stress on job satisfaction. For the company should know what factors that influence the achievement of job satisfaction. Based on the results of financial compensation research and work  motivation  positively  affect  the  job  satisfaction,  should  provide  compensation  in accordance  with  what  is  done  by  employees  /  employees.  This  will  trigger  employee motivation to work better again in the future. When sufficient financial compensation and the achievement  of a good work motivation  will suppress  the role of stress that is owned by employees, the situation will lead to good employee satisfaction.